The Biology of Lactoferrin, an Iron-Binding Protein That Can Help Defend Against Viruses and Bacteria - Kell, Douglas B.; Heyden, Eugene L.; Pretorius, Etheresia (Frontiers in Immunology, 2020)
Lactoferrin is a nutrient classically found in mammalian milk. It binds iron and is transferred into and between cells, serum, bile and cerebrospinal fluid, via a variety of receptors. It has important immunological properties, and is both antibacterial and antiviral. In particular, there is evidence that it can bind to at least some of the receptors used by coronaviruses and thereby block their entry. It may consequently be of preventive and therapeutic value during the present COVID-19 pandemic.